Amparo Dávila’s El huésped, from anxiety to horror - Evangelista Ávila, Iram Isaí (2018)
This article discusses the idea of horror in Amparo Dávila’s short Story El huésped from different points of view. First, it attempts to demostrate how the protagonist from Amparo Dávila’s short-story goes through the stages of anguish and anxiety within the plot of the story, all of which will lead her to horror. Likewise, the representation of the antagonist is suggested as an entity that carries a double meaning in the development of the narrative. It also discusses how the plot in a fantasy short story requires an active reader who will collaborate with the completion of the narrative. These distinctive features will be highlighted through the story analyzed here.